Bonding to dentin using an experimental zirconium oxynitrate etchant. (May 2021) - Mancuso, Edoardo; Comba, Allegra; Mazzitelli, Claudia; Maravic, Tatjana; Josic, Uros; Del Bianco, Federico; Tay, Franklin R.; Breschi, Lorenzo; Mazzoni, Annalisa
Abstract: Objective: To investigate, by means of microtensile bond strength test (μTBS), nanoleakage expression analysis (NL), gelatin zymography and in situ zymography, the effects of an experimental metal salt-based zirconium oxynitrate etchant [ZrO(NO3 )2, ] – ZON with two simplified adhesives on long-term bond strength and endogenous enzymatic activities. Methods: Middle/deep coronal dentin surfaces (N = 32) were conditioned either with a traditional 37 % H3 PO4 etchant (TE) or with ZON. Further, a single-component etch-and-rinse adhesive (EF) or a universal adhesive (AU) were applied and μTBS and NL tests were performed. Additional freshly extracted teeth were processed for gelatin zymography and in situ zymography evaluation. The tests were performed at baseline and (T0) and after 1-year-aging (T12). Bond strength and in situ zymography results were analyzed using analysis of variance (ANOVA) (three-way and one-way, respectively), while Chi-squared test was used for the NL results. Statistical significance was preset at α = 0.05. Results: All the investigated factors (adhesive system, dentin conditioner and aging) significantly influenced μTBS, with the AU and ZON performing better compared to EF and TE, respectively, and with lower bond strength values after aging (p < 0.05). Incremented silver nitrate deposits were observed at the adhesive interfaces after aging, especially for the TE groups (p < 0.05). Further, the experimental groups treated with ZON had significantly lower levels of enzymatic activity compared to TE, as shown by gelatin and in situ zymography (p < 0.05). Conclusions: The experimental etchant demonstrated promising results in hybrid-layer preservation over time when used with simplified bonding systems, and could therefore be recommended in the clinical practice.